Endocytic and autophagic pathways crosstalk in plants. (December 2015) - Zhuang, Xiaohong; Cui, Yong; Gao, Caiji; Jiang, Liwen
Highlights: ESCRT machinery and Rab GTPases play conserved and unique roles in mediating MVB/PVC to vacuole protein trafficking. SH3P2 mediates autophagic degradation via association with the autophagy machinery. The ESCRT component FREE1 interacts with SH3P2 to crosstalk with the autophagy pathway and regulates autophagic degradation. Abstract : The vacuole is the central site for both storage and metabolism in plant cells and mediates multiple cellular events during plant development and growth. Cargo proteins are usually sequestered into membrane-bound organelles and delivered into the vacuole upon membrane fusion. Two major organelles are responsible for the recognition and transport of cargos targeted to the vacuole: the single-membrane multivesicular body (MVB) or prevacuolar compartment (PVC) and the double-membrane autophagosome. Here, we will highlight recent discoveries about MVB/PVC-mediated and autophagosome-mediated protein trafficking and degradation, and will pay special attention to a possible interplay between the endocytic and autophagic pathways in regulating vacuolar degradation in plants.